Analysis of Soil Fertility and Sustainability of Shallot Intensive Farming - Nugraha, Septian Hadi; Suryaningtyas, Dyah Tjahyandari; Hariyadi, Hariyadi (Universitas Diponegoro, 2025)
Larangan District is one of the shallot-producing areas that the government prioritizes for agricultural intensification. The high intensity of agriculture in Larangan District causes soil fertility and sustainability disparities. This research evaluates soil fertility and the sustainability of shallot farming intensification activities in Larangan District, Brebes Regency. Soil fertility evaluation used two different approaches: Base Cation Saturation Ratio (BCSR), which referred to Koppitke & Menzies research in 2007 and assessment through a combination of soil chemical properties, as referred to Soil Research Center of Indonesia. Sustainability analysis was carried out using the Rapid Appraisal for Farming (RAP-Farm) approach with a multi-aspect sustainability analysis method, with a total of 6 aspects (ecological, economic, social, institutional, technological, and logistics, and infrastructure) with 36 factors. The results of the research show that Larangan District has a moderate soil fertility status, with a nutrient unbalance from cation ratio analysis. Sustainability status shows a less sustainable status with aspects that have values below the limit, namely ecology, economics, and technology.